In Search of Excellence versus The 100 Best Companies to Work for in America: A Question of Perspective and Values - Mitchell, Terence R. (Academy of Management Review, 1985)
The article presents reviews of two books, “In Search of Excellence,” by T. J. Peters and R. H. Waterman, and “The 100 Best Companies to Work for in America,” by Ralph Katz, Milton Mokowitz, and Robert Levering.